2000
DOI: 10.1016/s0014-5793(00)01796-8
|View full text |Cite
|
Sign up to set email alerts
|

Two genes encoding distinct cytosolic glutamine synthetases are closely linked in the pine genome

Abstract: The major isoenzyme of glutamine synthetase found in leaves of angiosperms is the chloroplastic form. However, pine seedlings contain two cytosolic glutamine synthetases in green cotyledons: GS1a, the predominant isoform, and GS1b, a minor enzyme whose relative amount is increased following phosphinotricin treatment. We have cloned a GS1b cDNA, and comparison with the previously reported GS1a cDNA sequence indicated that they correspond to separate cytosolic GS genes encoding distinct protein products. Phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…It has been proposed that the gain of a N-terminal transit peptide in GS2 would provide adaptive advantages to plants through enhanced photorespiratory ammonium assimilation in the plastids [12]. Members of the GS1 clade in angiosperms are grouped in subfamilies as previously reported by others [6,10,21]. PtGS1.2 and PtGS1.3 duplicates were found associated to these subfamilies suggesting they could play similar functions to those described for these isoforms.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It has been proposed that the gain of a N-terminal transit peptide in GS2 would provide adaptive advantages to plants through enhanced photorespiratory ammonium assimilation in the plastids [12]. Members of the GS1 clade in angiosperms are grouped in subfamilies as previously reported by others [6,10,21]. PtGS1.2 and PtGS1.3 duplicates were found associated to these subfamilies suggesting they could play similar functions to those described for these isoforms.…”
Section: Discussionmentioning
confidence: 66%
“…Recently it has been reported that plant GS holoenzyme has a decameric structure composed of two face-to face pentameric rings of subunits, with active sites formed between every two neighboring subunits within each ring [4,5]. Phylogenetic studies of nucleotide and amino acid sequences have shown that genes for chloroplastic and cytosolic GS in plants form two sister groups with a common ancestor which diverged by duplication before the split between angiosperms and gymnosperms [6]. …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report of a duplication of a plastid located gene, and interestingly, the duplication seems to be quite recent in view of the estimation of the age of divergence of the cytosolic GS genes. Studies in Pinus sylvestris , estimate that the duplication of an ancestral cytosolic GS occurred long before the divergence of gymnosperms/angiosperms [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Two different genes, GS1a and GS1b , encode GS1 isoforms in pine, and the isoforms exhibit distinct molecular and kinetic properties (Avila et al. , 1998; Avila‐Sáez et al. , 2000; de la Torre et al.…”
Section: Introductionmentioning
confidence: 99%